Causal Loop Diagrams: Little Known Analytical Tool | iSixSigma - Rushing, William (2010)
The causal loop diagram is an analytical tool that is seldom used in S ix Sigma but nonetheless is still very valuable. It is a foundational tool used in system dynamics, a method of analysis used to develop an understanding of complex systems.